Selective allocation of patients with vaginal apical prolapse to either mesh augmented open abdominal repair or vaginal sacrospinous colpopexy improve functional and anatomical outcomes - Hassan, Mahmoud F.; El-Tohamy, Osama; Yehia, Amr Helmy; Alghanimi, Salha A.; Al-Enezi, Hessa; Moussa, Mahmoud (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To evaluate the functional and anatomical outcomes after allocation of patients with apical vaginal prolapse to either mesh augmented abdominal repair or vaginal sacrospinous-colpopexy based on proposed selection criteria. Methods: A non-randomized trial was conducted at Ain-Shams university maternity hospital on patients with apical vaginal prolapse stage ≥2 based on pelvic organ prolapse quantification system. Certain criteria were proposed for patient selection to either mesh augmented abdominal repair or vaginal sacrospinous-colpopexy. Seventy-eight patients were assigned for sacrospinous-colpopexy and 47-patients for abdominal repair. Primary outcomes were the functional outcome using urogenital distress inventory questionnaire and patient global impression of improvement (PGI-I). Both were measured at 1-year’s follow-up. Secondary outcomes involved the anatomical success (defined as no apical prolapse ≥POP-Q stage 2), perioperative data and long-term complications. Results: There was improvement in all UDI domains for sacrospinous-colpopexy and abdominal repair groups with genital prolapse domain of median (interquartile range) 0 (0-10), 0 (0-0) respectively. Eighty-nine percent of abdominal repair group and 85% of sacrospinous-colpopexy group reported scale of 1 or 2 on PGI-I scale at 1-year follow-up. PGI-I score and improvements in UDI domains were maintained till 5-year follow-up. The anatomic success rate at 1-year follow-up was 97.9% in abdominal repair group and 78.2% in the sacrospinous-colpopexy group. No long-term mesh complications were detected in mesh augmented abdominal repair over the whole follow-up periods. Conclusion: The resulting meritorious functional and anatomical outcomes favor adoption of our proposed selection criteria in the initiation of guidelines and recommendations for managing vaginal apical prolapse.